Emergence and Recovery of Ceftazidime-avibactam Resistance in blaKPC-33-Harboring Klebsiella pneumoniae Sequence Type 11 Isolates in China. (23rd December 2020) - Shi, Qingyu; Yin, Dandan; Han, Renru; Guo, Yan; Zheng, Yonggui; Wu, Shi; Yang, Yang; Li, Shirong; Zhang, Rong; Hu, Fupin
Abstract: This is the first report of ceftazidime–avibactam resistance caused by the bla KPC-33 mutation through the D179Y variant during the treatment of bla KPC-2 -positive Klebsiella pneumoniae -related infections in China. The bla KPC-33 -containing K. pneumoniae was susceptible to meropenem–vaborbactam, cefepime–zidebactam, tigecycline, and polymyxin B. The bla KPC-33 gene was located on a 77 551-bp transformable plasmid harboring qnrS1 and bla LAP-2 . Detecting bla KPC-33 -positive K. pneumoniae clinical strains is important for infection control.